1990
DOI: 10.1042/cs0780621
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of protein metabolism after elective surgery in patients receiving constant nutritional support

Abstract: 1. The present study was designed in an attempt to resolve conflicting views currently in the literature relating to the effect of surgery on various aspects of protein metabolism. 2. Sequential post-operative (2, 4 and 6 days) changes in whole-body protein turnover, forearm arteriovenous difference of plasma amino acids, glucose, lactate and free fatty acids, muscle concentration of free amino acids, RNA and protein, urinary nitrogen and 3-methylhistidine, plasma concentrations of insulin, cortisol and growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Urinary nitrogen losses in both groups did not exceed those found in normal healthy volunteers during several days of hypocaloric parenteral nutrition (approximately 11 g nitrogen per day) 23 . This is in contrast to the accelerated nitrogen losses seen during the first few days after major abdominal surgery in traditional practice (approximately 12-16 g nitrogen per day) 24,25 . Furthermore, nitrogen balance was achieved in patients given complete enteral feed, which is also in contrast to the negative nitrogen balance reported during 1-4 days after major abdominal surgery in traditional care with enteral 26 or even parenteral 27 nutrition.…”
Section: Discussionmentioning
confidence: 89%
“…Urinary nitrogen losses in both groups did not exceed those found in normal healthy volunteers during several days of hypocaloric parenteral nutrition (approximately 11 g nitrogen per day) 23 . This is in contrast to the accelerated nitrogen losses seen during the first few days after major abdominal surgery in traditional practice (approximately 12-16 g nitrogen per day) 24,25 . Furthermore, nitrogen balance was achieved in patients given complete enteral feed, which is also in contrast to the negative nitrogen balance reported during 1-4 days after major abdominal surgery in traditional care with enteral 26 or even parenteral 27 nutrition.…”
Section: Discussionmentioning
confidence: 89%
“…6 When comparing intravenous with volatile GA, it has been reported that propofol combined with remifentanil inhibits the ACTHecortisol axis and catecholamine and growth hormone increase compared to volatile GA. 7 Metabolic changes secondary to surgical stress include an increase in proteolysis after surgery, leading to muscle breakdown and loss. 8 The use of a combined spinal and epidural blockade during hip surgery has been shown to attenuate the increase in amino acid oxidation 24 hours after surgery, in comparison to GA. 9 Among GA reagents, the use of propofol has been found to cause a reduction in the proteolytic response to surgery, by potentially allowing the body to make use of triglycerides contained within the propofol emulsion as a substitute. 10 The increase in glucose production during surgery can also be prevented by epidural analgesia, yet inhaled anesthetics appear to have no effect.…”
Section: Surgical Stress Responsementioning
confidence: 99%
“…The mechanisms by which nutrition modulates protein metabolism are still not completely defined, but the assumption underlying clinical practice and metabolic research is that injury provokes a metabolic response characterized by unavoidable net protein breakdown that can be reduced with proper nutritional support (Carli et al, 1990;Jeevanandam et al, 1991;Romito, 1995;Waterlow, 1995;Hasselgren and Tiao, 1996).…”
Section: Introductionmentioning
confidence: 99%